Science, Technology, Engineering and Mathematics(STEM) Teachers Attitudes towards technology use in teaching in Bangladesh - Abdullahi Binta Suleiman (International Journal of Engineering Education, 2022)
Given the popularity gained by ICT in universal education in the past two decades, as new capabilities for technology integration emerged, its use in educational contexts has steadily increased. The use of technology for a broad range of teaching and learning purposes is now established at many universities. Studies were conducted about technology use attitude in education, but the majority has concentrated on how to replace traditional with blended methods of instructions. This study examines Science Technology Engineering and Mathematics (STEM) teachers’ attitude towards technology use in teaching in Bangladesh. A descriptive research design was used.  Research instrument employed was questionnaire which was administered on 120 STEM teachers from three sampled universities of Bangladesh. It was found that the respondents’ affective, perceived usefulness, behavioural intentions, and overall attitude towards technology use were significant, though challenges that include domain (affective, cognitive, perceived control), conceptualization of technology use attitude, teacher-training, objectives and contents were obtained. In essence, the study findings revealed a positive attitude of the STEM teachers towards technology use in teaching in Bangladesh universities and challenges needed to be overcome for better teacher delivery. A technology acceptance model formulated by Venkatesh and others (UTAUT) which hypothesized on user acceptance of technology towards a unified view was used in this study. The theory wants to explain user intentions to use technology following behavioral intensions. The constructs of UTAUT (performance expectancy PE, effort expectancy EE, social influence SI and the facilitating condition FC) are found to have positive effect on behavoiural intension and the attitude of technology use in teaching as well. Attitude is the most important detector of behavioural intension towards the use of technology by STEM teachers (Troy et. al 2013).